A critical study on applicability of sokoban game for building cognitive model of a student for career assessment - Chandra Prakash, V.; Sastry, J. K. R.; Rao, V.Kantha; Vineetha, T.; Harika, V.; Abhishek Reddy, A. (International Journal of Engineering and Technology, 2017)
Career assessment is extremely important for a student to choose the best career in his/her life. A career counsellor may assess a student by considering his/her academic record and the scores obtained in IQ tests, reasoning, quantitative-aptitude, etc. and suggest a suitable career. After studies, when the student gets employment in his/her selected career, at times, the student may find it very difficult to continue in his/her career. A major reason may be that the psychology of the student may not match with the psychology that is expected for the chosen career. Hence, it is highly essential for the counsellors to assess the psychological factors of a student before suggesting a suitable career. Game playing is one method through which psychological factors of a student can be assessed. This paper presents a critical study on applicability of Sokoban game for assessing student’s psychological factors so that an Expert system can build a cognitive model of a student for career assessment.